Republic of Serbia : Seventh Review and Inflation Consultation Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2011)
The global financial crisis unmasked Serbia's unsustainable pre-crisis growth model. Looking back, the Stand-By Arrangement (SBA) provided effective insurance against a financial meltdown, initiated the needed re-balancing of the economy, but could not prevent large job losses. Looking ahead, the transition to a more sustainable growth model remains incomplete and fragile. The export-led recovery is expected to continue picking up steam, but labor market conditions will remain difficult. The current account deficit is expected to remain relatively high, requiring significant capital inflows to maintain external balance.